Ambulatory blood pressure in the dash diet trial: Effects of race and albuminuria. Issue 2 (31st January 2018) - Tyson, Crystal C.; Barnhart, Huiman; Sapp, Shelly; Poon, Victor; Lin, Pao‐Hwa; Svetkey, Laura P.
Abstract : We evaluated whether low‐grade albuminuria or black race modulates ambulatory blood pressure (BP) or nocturnal BP response to the DASH diet. Among 202 adults enrolled in the DASH multicenter trial who were fed the DASH or control diet for 8 weeks, reductions in 24‐hour daytime and nighttime SBP and DBP were significantly larger for DASH compared to control. Median changes in nocturnal BP dipping were not significant. Compared to urine albumin excretion of <7 mg/d, ≥7 mg/d was associated with larger significant median reductions in 24‐hour SBP (−7.3 vs −3.1 mm Hg), all measures of DBP (24‐hour: −5.9 vs −1.8 mm Hg; daytime: −9.9 vs −4.0 mm Hg; nighttime −9.0 vs −2.0 mm Hg), and with increased nocturnal SBP dipping (2.3% vs −0.5%). Black race was associated with larger median reduction in 24‐hour SBP only (−5.5 vs −2.4 mm Hg). This analysis suggests greater effect of DASH on ambulatory BP in the presence of low‐grade albuminuria.